A Review article on Staphylococcus haemolyticus (International Journal of Scientific Research and Management (IJSRM), 2025)
Staphylococcus haemolyticus is a newly-associated OPP which is a major concern to the immunocompromised patients. The key points from the search results are: The key points from the search results are: Thus, S. haemolyticus can attach and penetrate the primary human skin fibroblast cells with an emerge in cytotoxicity and additional level of apoptosis. It possesses seem to encode factors of virulence that cause enterotoxins and alpha-hemolysin. S. haemolyticus is the second, or third if S. epidermidis is considered, among the coagulase-negative Staphylococcus most frequently isolated from clinical samples, being an agent of hematogenous and device-associated infections. It has a high propensity to cause resistance to antimicrobials particularly glycopeptides though treatment options are limited. S. haemolyticus Clinical strains of the S. haemolyticus are more virulent than skin originated isolates, more prone to form biofilms, and at least to Oxacillin and Aminoglycoside. S. haemolyticus is one of the significant pathogens of neonates, which affects primarily in the late onset sepsis, and has increased prevalence of multidrug-resistant strains in certain places.